Metabolism of 2-oxo-clopidogrel to the clopidogrel active H4 metabolite using human liver microsomes and its inhibitory effect on ADP-induced human platelet aggregation ex vivo: a confirmatory, placebo-controlled, parallel-group study - Christian Schulz; Steffen Braune; Christof Mrowietz; Jan-Heiner Küpper; Friedrich Jung (Frontiers in Cardiovascular Medicine, 2026)
Clopidogrel is a drug that is commonly used to prevent occlusive events after coronary artery interventions. However, the efficacy of clopidogrel varies depending on the CYP2C19 polymorphism, as it is not clopidogrel itself but the H4 metabolite that is responsible for the pharmacological effect. Carriers of the CYP2C19 loss-of-function allele genotype – which can affect up to 50% of patients - exhibited a higher likelihood of experiencing cardiovascular events. Administering the H4 metabolite directly avoids this problem. In the first step, the H4 metabolite was successfully produced in vitro from 2-oxo-clopidogrel using human liver microsomes. Thereafter, human platelet-rich plasma was supplemented with the H4 metabolite and then stimulated with adenosindiphosphate (ADP, 20 µM). The present confirmatory, placebo-controlled, parallel-group ex vivo study showed that the H4 metabolite of clopidogrel metabolized by human liver microsomes significantly and relevantly inhibited ADP-induced platelet aggregation. The study thus showed that the H4 metabolite of clopidogrel produced by human liver microsomes completely overcomes the limitations of clopidogrel, such as high inter-individual variability due to genetic polymorphisms of CYP2C19, a delayed onset of action and inadequate efficacy.